Propionicicella superfundia gen. nov., sp. nov., a chlorosolvent-tolerant propionate-forming, facultative anaerobic bacterium isolated from contaminated groundwater - Bae, Hee-Sung (2006)
A novel strain, designated as BL-10T, was characterized using a polyphasic approach after isolation from groundwater contaminated by a mixture of chlorosolvents that included 1,1,2-trichloroethane, 1,2-dichloroethane, and vinyl chloride. Stain BL-10T is a facultatively anaerobic bacterium able to ferment glucose to form propionate, acetate, formate, lactate, and succinate. Fermentation occurred in the presence of 1,2-dichloroethane and 1,1,2-trichloroethane at concentrations to at least 9.8 and 5.9 mM, respectively. Cells are Gram-positive, rod-shaped, non-motile, and do not form spores. Oxidase and catalase are not produced and nitrate reduction did not occur in PYG medium. Menaquinone MK-9 is the predominant respiratory quinone and meso-diaminopimelic acid is present in the cell wall peptidoglycan layer. Major cellular fatty acids are C15:0, iso C16:0, and anteiso C15:0. Genomic DNA G+C content is 69.9 mol%. Phylogenetic analysis based on 16S rRNA gene sequence comparisons showed strain BL-10T to fall within the radiation of genera Propionicimonas and Micropruina. On the basis of the results obtained in this study, it is proposed that strain BL-10T should be classified as a novel taxon, for which the name Propionicicella superfundia gen. nov., sp. nov. is proposed. The type strain of Propionicicella superfundia is BL-10T (=ATCC BAA-1218T, =LMG 23096T).1